Repeatability and interobserver reproducibility of Artemis-2 high-frequency ultrasound in determination of human corneal thickness - Ogbuehi KC; Osuagwu UL (Clinical Ophthalmology, 2012)
Kelechi C Ogbuehi, Uchechukwu L OsuagwuOutpatient Clinic, Department of Optometry, King Saud University, Riyadh, Kingdom of Saudi ArabiaBackground: The purpose of this study was to assess the repeatability and limits of agreement of corneal thickness values measured by a high-frequency ultrasound (Artemis-2), hand-held ultrasound pachymeter (DGH-500) and a specular microscope (SP-3000P).Methods: Central corneal thickness (CCT) was analyzed in this prospective randomized study that included 32 patients (18 men and 14 women) aged 21–24 years. Measurements were obtained in two sessions, one week apart, by two examiners with three devices in a randomized order. Nine measurements were taken (three with each device) on one randomly selected eye of each patient in each measurement session. The coefficient of repeatability and interobserver reproducibility for the values of each method were calculated. The limits of agreement between techniques were also evaluated.Results: There were no significant differences in CCT values between sessions for each of the three devices (P > 0.05). The repeatability coefficients for the Artemis-2 (±8 µm/±9 µm) were superior to those of the SP-3000P (±9 µm/±11 µm) and DGH 500 (±12 µm/±12 µm) in session 1/session 2 respectively, while the interobserver reproducibility index (differences between session 1 and session 2) was superior for the SP-3000P (±17 µm) with respect to DHG-500 (±29 µm) and the Artemis-2 (±31 µm). In session 1 and session 2, the limits of agreement between the techniques were 35 µm to -31 µm and 34 to -20 µm, respectively, for DGH-500 versus Artemis-2, 73 µm to 3 µm and 60 µm to 9 µm for Artemis-2 versus SP-3000P, and 58 µm to 22 µm and 72 µm to 10 µm for DGH-500 versus SP-3000P comparisons. The DGH-500 and Artemis-2 gave similar values (P > 0.05) in both sessions, but both (Artemis-2 and DGH-500) values were significantly greater than that of the SP-3000P (P < 0.05) in both sessions.Conclusion: Repeatability was comparably good for the three techniques. However, interobserver reproducibility was approximately twice as good with the SP-3000P compared with the other two devices. The Artemis-2 CCT values consistently agreed with the DGH-500 and less so with the SP-3000P. The Artemis-2 provided CCT values that were, on average, 38 µm and 34 µm greater than that of the SP-3000P in session 1 and session 2, respectively.Keywords: cornea thickness, Artemis-2 ultrasound, hand-held ultrasound, SP-3000P noncontact specular microscopy, reproducibility